How perceived autonomy support and controlling coach behaviors are related to well- and ill-being in elite soccer players: A within-person changes and between-person differences analysis - Cheval, B.; Chalabaev, A.; Quested, E.; Courvoisier, D. S.; Sarrazin, P. (Psychology of Sport and Exercise, 2017)
Objectives: Grounded in Basic Psychological Needs Theory (Ryan & Deci, 2002), this study examined the temporal relationships between perception of coaches' autonomy support and different facets of controlling behaviors, the satisfaction-frustration of athletes' basic needs, and subjective vitality, self-esteem and burnout in elite sportsmen. Methods:Participants (N = 110 males) from three elite youth soccer academies in northwest France completed a questionnaire on three occasions during the last three months of the competitive season. Results: Linear mixed models revealed that perceptions of coach-autonomy support and only two facets of controlling coach behaviors (excessive personal control and negative conditional regard) were related to basic need satisfaction-frustration, which in turn were related to the indices of well- and ill-being. In most cases, the relationships were observed both at the within- and between-person levels, but some were observed only at one level. Conclusions: The findings highlight the importance of considering the different facets of controlling coach behaviors separately and disaggregating the between-person and within-person effects.